Impact of Urology Trainee Debt Levels on Future Practice Choices and Expectations. Issue 2 (28th March 2021) - Harris, Andrew M.; Fang, Raymond; Sadowski, Dan; Meeks, William; Makarov, Danil; McKenna, Patrick; Pruthi, Raj; Gonzalez, Chris; Schlossberg, Steven; Gettman, Matthew; North, Amanda
Abstract: Introduction: Excessive trainee debt continues to be a problem. Little is known about how debt influences future practice decisions. We sought to examine the correlation between educational debt and anticipated practice choices and career expectations to better understand the impact of debt on urology trainees to inform urology workforce policy. Methods: Data were collected from urology trainees who completed the AUA Annual Census between 2016 and 2018. We examined level of debt among urology trainees against their anticipated practice choices compensation expectation and various debt relief variables. Results: Among 705 U.S. urology trainees who completed the survey, 22% had no debt, 23% had <$150, 000 debt, 27% had $150, 000 to $250, 000 of debt, and the remaining 27% had >$250, 000. Debt level did not appear to significantly affect anticipated future practice setting or the decision to pursue fellowship. Concerning how loan forgiveness influenced practice opportunity, 31% of trainees reported no effect, 42% some effect and 27% great effect. Those trainees with higher level of debt appeared to be more likely to accept a practice opportunity if loan forgiveness was offered (p ≤0.001). Those trainees with higher level of debt were more likely to anticipate higher annual compensation as compared to those with less debt (p=0.001). Conclusions: Nearly 70% of those trainees with debt had $150, 000 of debt or higher. Our study showed carrying educational debt is statistically associated with trainees' choice of anticipated practice for better compensation and tuition forgiveness. Workforce policy should consider addressing the financial burden of urology trainees.